Novel N‐Acyl‐1H‐imidazole‐1‐carbothioamides: Design, Synthesis, Biological and Computational Studies. Issue 3 (20th February 2020) - Aziz, Hamid; Saeed, Aamer; Khan, Muhammad Aslam; Afridi, Shakeeb; Jabeen, Farukh; Ashfaq‐ur‐Rehman,; Hashim, Muhammad
Abstract: The present study reports the convenient synthesis, spectroscopic characterization, bio‐assays and computational evaluation of a novel series of N ‐acyl‐1 H ‐imidazole‐1‐carbothioamides. The screened derivatives displayed excellent antioxidant activity, moderate antibacterial and antifungal potential. The screened derivatives were found to be highly biocompatible against hRBCs. Molecular docking ascertained the mechanism and mode of action towards the molecular target delineating that ligands and complexes were stabilized at the active site by electrostatic and hydrophobic forces in accordance to the corresponding experimental results. Docking simulation provided additional information about the possibilities of inhibitory potential of the compounds against RNA. Computational evaluation predicted that N ‐acyl‐1 H ‐imidazole‐1‐carbothioamides 5c and 5g can serve as potential surrogates for hit to lead generation and design of novel antioxidant and antibacterial agents. Abstract :